Optimalisasi Suhu di Inkubator untuk Penyimpanan Isolat Jamur Trichoderma Sp. di Laboratorium Fitopatologi - Junita, Armi; Nurhayani, Nurhayani; Afridayanti, Neny (Seminar Nasional Lahan Suboptimal, 2022)
Junita A, Nurhayani N, Afridayanti N. 2022. Temperature optimization in the incubator for fungi isolate storage Trichoderma Sp. at the laboratory of Phytopathology. 2022. Tulis judul makalah yang dipresentasikan di seminar ini. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 847-858. Palembang: Penerbit dan Percetakan Universitas Sriwijaya (UNSRI). Trichoderma is one of the fungi as ingredient main used for practicum and research in the laboratory, one of the practicum courses in the plant protection department is the concentration of disease in plants, disease practicum always requires fungal isolates for identification. The method is a randomized block design with two treatment factors. The first factor is incubator temperature of 24, 28 and 30 oC, and the second factor is storage time of 10, 20 days, and 1 month. Variables measured were fungal colony diameter, thickness of mycelium, and color of morphology of Trichoderma sp. The isolates tested were Trichoderma sp. with 10 replicates which were then stored in an incubator with a predetermined temperature, the observation time was carried out for three months. The purpose was to determine the effect of the incubator temperature for the growth of Trichoderma sp. on the length of storage, so that it could facilitate the course of practicum and research with sufficient availability of fungi collections in the laboratory. The benefit of this research is that the laboratory manager can find out the optimal temperature and storage time in the incubator for the collection of Trichoderma sp. Based on observations from this study, it is known that the best temperature for storage of Trichoderma sp. namely at a temperature of 30 oC with the diameter of the fungus growing faster, more spores and the morphological color of the fungus Trichoderma sp. brighter.